Glomus tumour of the male urethra: an unusual diagnostic. Issue 11 (25th November 2019) - Ramsay, Sophie; Chan, Garson; Zimmerman, W Britt; Chee, Justin
Abstract : A 56-year-old man was referred to a reconstructive urologist for evaluation of a tender nodule in the penoscrotal area. Penile Doppler ultrasound showed a non-compressible mass with internal vascularity within the corpora spongiosum, and MRI identified an enhancing, solid mass arising from the ventral aspect of the urethra. Surgical resection warranted partial excision and reconstruction of the urethra, which was achieved by a dorsal onlay buccal mucosal graft urethroplasty through a perineal incision with penile invagination. The histopathology report concluded to an invasive, high-grade urothelial carcinoma, for which an aggressive oncological approach was considered. However, discussion with the pathology team led to the identification of a glomus tumour for which the patient did not need additional procedures. Urethral glomus tumours are extremely rare and should be included in the differential diagnosis of urethral masses. This case exemplifies the importance of teamwork in the management of uncommon cases.